Sistem Informasi Parenting Menggunakan Metode Design Thinking dan Personal Extreme Programming - Muhammad Awaluddin; Royana Afwani; Budi Irmawati (Jurnal Teknik Informatika dan Sistem Informasi, 2022)
Character education is a continuous process that requires a continuous process. The family environment is the first place for children to learn about character education. During their growth period, children will learn every basic behavior that is important for their life. Children's mental and emotional are strongly influenced by the ability and understanding of parents regarding parenting. Because of this, the role of parents is very important, but currently, most parents do not have the ability and understanding regarding good parenting according to the needs and development of children. Based on interviews conducted with 40 parents with children aged 0-6 years, 85% of them said that it was still difficult to know how to adopt an appropriate parenting style based on the age and development of the child's character. Seeing these problems, this research was conduct to develop the socio-emotional character of children by providing assistance, activity recommendations, and character development milestones based on the child's age. This research was conducted to provide recommendations for more personalized activities according to the needs of children. The research was conducted using the design thinking method to validate problems and solutions. By using the design thinking method, a validated solution can be formed because through each process it can be known what is the most pain (toughest problem) and most gain (biggest desire) from the customer regarding the problems experienced. These recommendations are then packaged in a software using a personal extreme programming approach.